The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/su11133511
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Improved Multifunctional Landscape Use: Trails as Facilitators for Collaboration Among Stakeholders

Abstract: Trails are significant features in landscapes, and many ancient pathways have developed into routes of great importance for recreation and tourism in contemporary societies. Nevertheless, international research on recreational trails has hitherto mainly focused on managerial and environmental aspects of trails and less on trails from a social science perspective, such as conflict management. This study explores the role of recreational trails as a potential tool for managing conflicts in a multifunctional land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…From the experience of Lijia, through negotiation and dialogue, governments, firms and villagers have found it easier to reach a consensus and to develop multifunctional goals. Some studies in the literature have improved upon this [51]. In the phase of capitalization, three types of valuable stock land can be changed.…”
Section: Discussionmentioning
confidence: 99%
“…From the experience of Lijia, through negotiation and dialogue, governments, firms and villagers have found it easier to reach a consensus and to develop multifunctional goals. Some studies in the literature have improved upon this [51]. In the phase of capitalization, three types of valuable stock land can be changed.…”
Section: Discussionmentioning
confidence: 99%
“…This is a call to action for policymakers, communities, and individuals to recognize the intrinsic value of these areas and to implement innovative strategies that protect and celebrate their unique characters [124]. By doing so, we ensure that cultural landscapes remain vibrant and significant for future generations, bridging the past with the present and the future in a continuous narrative of human interaction with the land [125]. Moreover, the preservation of cultural landscapes offers an opportunity to advance environmental sustainability and resilience.…”
Section: Maintaining the Integrity And Relevance Of Cultural Landscapesmentioning
confidence: 99%
“…As outdoor recreation grows in space and throughout different seasons, and crowding manifests, concerns around conflicts among user groups have also increased. Although limited (Godtman Kling et al 2017Kling et al , 2019, research has shown that potential conflicts may arise due to scarce resources or capacity issues (Haddock and Quinn 2015), a difference in values among user groups (Vaske et al 2007), and the perceived or actual environmental impacts of different activities (see Switalski 2018).…”
Section: Mountainagendamentioning
confidence: 99%